(untitled) (Gaceta Técnica, 2018)
In the present work of investigation the numerical behavior of structural profiles of steel of thin wall is studied, of Venezuelan national production Conduven ECO, of square cross section, constructed in the form of beam type cantilever, under the effects of Fatigue of Ultra-Low Cycling. Experimental tests were carried out where histories of cyclic displacements were applied, with very low speed and acting in a range that goes from the yielding effort to the last effort of the element, obtaining a degradation of the resistant capacity of the profiles, these experimental results were compared with the numerical simulations made through a commercial program of finite elements, obtaining satisfactory results.